Remarks on the Representation Theory of the Moyal Plane - J. M. Isidro; P. Fernández de Córdoba; J. M. Rivera-Rebolledo; J. L. G. Santander (Advances in Mathematical Physics)
We present an explicit construction of a unitary representation of the commutator algebra satisfied by position and momentum operators on the Moyal plane.